Spectrum of Genetic Variants in a Cohort of 37 Laterality Defect Cases - Antony, Dinu; Gulec Yilmaz, Elif; Gezdirici, Alper; Slagter, Lennart; Bakey, Zeineb; Bornaun, Helen; Tanidir, Ibrahim Cansaran; Van Dinh, Tran; Brunner, Han G.; Walentek, Peter; Arnold, Sebastian J.; Backofen, Rolf; et al. (Frontiers in Genetics, 2022)
Laterality defects are defined by perturbed left-right arrangement of organs in the body, occurring in a syndromal or isolated fashion. In humans, Primary Ciliary Dyskinesia (PCD) is a frequent underlying condition, where ciliary motility defects also result in reduced airway clearance, frequent respiratory infections and infertility. Non-motile cilia dysfunction, and dysfunction of non-ciliary genes can also result in disturbances of the left-right body axis. Despite long-lasting genetic research, the mutation detection rate has remained surprisingly low. Here, we used Whole Exome Sequencing with Copy Number Variant (CNV) analysis to delineate the underlying molecular cause in 35 mainly consanguineous families with laterality defects. We identified causative variants in 14 families with majority of mutations detected in genes previously associated with PCD, including two small homozygous CNVs. None of the patients was previously clinically diagnosed with PCD, underlining the importance of genetic diagnostics for PCD diagnosis and adequate clinical management. Identified variants in non-PCD associated genes included PKD1l1 and PIFO, confirming that dysfunction of these genes results in laterality defects in humans. Further, we detected candidate variants in GJA1 and ACVR2B possibly associated with situs inversus. The low mutation detection rate, in line with other previously published studies, points towards existence of non-coding genetic variants, putative genetic mosaicism, epigenetic or environmental effects.